PENGARUH LITERASI KEUANGAN, GAYA HIDUP, DAN ELECTRONIC MONEY TERHADAP PERILAKU KONSUMTIF MAHASISWA GENERASI GEN-Z - Ferdy Shiega; Mas Intan Purba; Jodan Winston; Nur Aliah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to determine the effect of financial literacy, lifestyle, electronic money on the consumptive behaviour of generation z students at Prima Indonesia University. Consumptive behaviour can be explained by looking at the habits of the subject, in this case students, who more often buy goods to meet their wants rather than needs rather than saving or investing. Good financial literacy is expected to help all individuals carry out good financial behaviour. The reality that is often encountered today is the tendency of students who are late adolescents to imitate a consumptive lifestyle that is all up to date. Excessive use of e-money can trigger consumptive behaviour. Consumptive behaviour is associated with excessive consumption patterns of goods or services, beyond the limits of one's needs. The research method uses a quantitative method with a sample size of 100 students. Data collection was carried out through interviews, questionnaires and documentation studies. Data testing was carried out by conducting classical assumption tests, regression tests and hypothesis testing using SPSS. The results of the study showed partially and simultaneously that financial literacy, lifestyle, electronic money had a significant effect on consumptive behaviour.